Branched EHNBR and its properties with enhanced low-temperature performance and oil resistance. Issue 55 (9th October 2019) - Liang, Lu; Dong, Jianjun; Yue, Dongmei
Abstract : Epoxide nitrile butadiene rubber (ENBR) was prepared via in situ epoxidation from nitrile butadiene rubber (NBR) with acetic acid and hydrogen peroxide. Abstract : Epoxide nitrile butadiene rubber (ENBR) was prepared via in situ epoxidation from nitrile butadiene rubber (NBR) with acetic acid and hydrogen peroxide. ENBR had been selectively hydrogenated in the presence of a homogeneous Wilkinson catalyst. The hydrogenated epoxide nitrile butadiene rubber (EHNBR) and ENBR were characterized by infra-red and proton nuclear magnetic resonance. No change was noted in the epoxy content of the polymer after the reaction. The catalyst is highly selective in reducing carbon–carbon double bonds in the presence of epoxy groups. DSC analysis reveals the T g of ENBR varied linearly with molar epoxide content and the T g value increased by 0.82 °C per mol%. It also found that the introduction of epoxy groups can effectively reduce the extent of crystallization by impairing the regularity of the molecular chain, but crystalline structure was difficult to completely eliminate. Therefore, anhydrides were selected as ring-opening reagents to react with epoxy groups in EHNBR. The products, branched EHNBR, were characterized by infra-red and proton nuclear magnetic resonance. The conversion rate of the epoxide group was calculated by 1 H NMR. The glass transition temperature of EHNBR- g -heptyl group was −34.1 °C, and its DSC curve demonstrated no crystal structure. The coefficient of cold resistance under compression of EHNBR grafted propyl ester was 0.36, which represented a superior low-temperature performance. Furthermore, residual epoxy groups and ester groups extremely enhanced the oil resistance of HNBR.